Flash Sale Promotion to Increase Room Occupancy and Room Revenue at The Royal Beach Seminyak Bali - Ni Kadek Hera Silawati; I Putu Astawa; I Gusti Putu Sutarma; Made Sudiarta; Ida Ayu Elistyawati (International Journal of Travel, Hospitality and Events, 2023)
Purpose: This research aimed to describe the implementation of flash sale promotions and the contribution of flash sales to room occupancy and room revenue at The Royal Beach Seminyak Bali (TRBS). Research methods: The research uses interviews, observation, and documentation studies on the number of room nights per month data and room revenue from flash sales data for the last three years. The data analysis technique used is descriptive statistics processed with Microsoft Excel 2013. Results and discussion: Form of the implementation of the flash sale starts with a communication plan in the form of promotions that are carried out using several platforms such as websites, mobile applications, and social media. During the execution of the flash sale, the discounted price is adjusted to the guest who is an AccorHotels member and not an AccorHotels member. Implication: Implementing the flash sale promotion was quite helpful in increasing room occupancy and room revenue by contributing the third largest reservation with an average donation of 20% for room occupancy and 18% for room revenue over the last three years.   Keywords: hotel, flash sale promotion, room occupancy, room revenue.